A Bandeira Vermelha em números: uma análise sobre o semanário da Federação Maximalista Portuguesa (1919-1920) - Pina, André Costa (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2019)
Taking by reference the problematic on the foundation of the Portuguese Communist Party (PCP), we focused on advancing the knowledge on the first newspaper centered on Bolshevik propaganda in Portugal, A Bandeira Vermelha. In that journey, we gathered 420 texts from the weekly newspaper of the Portuguese Maximalist Federation, from 1919 and 1920, the period in which this newspaper was the organ of this organization. In this analysis we gathered texts from maximalist newspaper texts with the goal of verifying the representation of Portuguese writers by district, the frequency of certain topics and to precise the influence of French proto-Bolshevik authors in the Portuguese maximalists ideological goals.